Doctor-patient Narrative Re-discovered from Overseas Traditional Chinese Medicine Practices - Chengju SHEN; Yidan YANG; Zhenyi LI; Yang YANG (Chinese Medicine and Culture)
Abstract. The doctor-patient narrative has been revisited and appreciated in both the West and the East due to the negative impact of biochemical medicine in the past two centuries on healthcare. Biochemical medicine system simply marginalized the roles of doctors and patients. More research and practice of “doctor’s benevolence” and “humanistic medicine” have called for the return of the doctor-patient narrative. This paper draws on interviews with several non-Chinese overseas traditional Chinese medicine (TCM) practitioners, whose clients are also non-Chinese. We adopted discourse analysis to explore our data. We found that they actively engaged in doctor-patient narrative with localized interpretation of TCM. We believe such a return to basic doctor-patient narrative is caused by fundamental needs for doctor-patient narrative coinciding with loose control of TCM practices in the studied countries. This discovery may inspire further study on re-establishing doctor-patient narratives in healthcare institutions by re-positioning biochemical medicine.